Untangling an AGS Outbreak Caused by the Recombinant GII.12[P16] Norovirus With Nanopore Sequencing - Xiong, Qianling; Jiang, Huimin; Liu, Zhe; Peng, Jinju; Sun, Jing; Fang, Ling; Li, Caixia; Qiu, Ming; Zhang, Xin; Lu, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
For a rapidly spreading virus such as NoV (norovirus), pathogen identification, genotype classification, and transmission tracing are urgent for epidemic control. Here, we applied the Nanopore metatranscriptomic sequencing to the pathogen testing on anal swabs and supply water samples from a community AGS (Acute gastroenteritis) outbreak. The positive cases were also confirmed by RT-PCR. The NGS (Next Generation Sequencing) library was constructed within 8 hours and the real-time analyses were carried out during sequencing. The norovirus positive reads were detected from 13 of 17 collected samples, including two samples from supply water. The identical viral sequences from supply water samples and cases suggested the potential source of the outbreak. More important, a nearly complete viral genome generated from Nanopore sequencing suggested the outbreak was likely caused by a recombinant GII.12[P16] virus, which was previously identified in the United States in 2017 and Canada in 2018. This is the first report of this emerging recombinant norovirus in mainland China following the large outbreaks caused by the recombinant GII.17[P17] and GII.2[P16] in 2014 and 2016, respectively. Close monitoring of the prevalence of this new recombinant strain is required. Our data also highlight the importance of real-time sequencing in the outbreak caused by emerging pathogens.